MENDORONG LEGALITAS UMKM MELALUI PROGRAM PENGABDIAN PEMBUATAN NOMOR INDUK BERUSAHA - Widya Putri; Hilman Wiranata; Yesi Valentine; Alia Alia; Wella Adestia Fitri; Yogi Pranata; Wulan Sri Wahyuni; Azri Azri; Yuli Artha Hutagalung; Zara Alga Suri (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2026)
The problem of this research is the low ownership of Business Identification Number (NIB) among MSME actors which hinders access to legality, financing, and business development. The research objective is to help MSME actors obtain NIB as a form of business legality while providing an understanding of the benefits of NIB for business strengthening. The methods used were door-to-door socialization, data collection, and assistance in making NIB through the Online Single Submission (OSS) system, as well as direct training and counseling. The results showed a significant increase in the number of MSMEs that have NIB, so that MSMEs are more confident, obtain legal protection, and expand market networks, which ultimately support sustainable business growth and competitiveness.